The Secret of Chimneys - Christie, Agatha (London HarperCollins Publishers, 2001)
A young drifter finds more than he bargained for when he agrees to deliver a parcel to an English country house.
Keywords: Battle, Superintendent (Fictitious character) -- Detective and mystery stories -- England